Porphyrazines with appending eight crown ethers - Sağlam, Özgül; Gül, Ahmet (Elsevier BV, 2001)
Abstract Porphyrazines (M=2H, Mg, Cu, Co or Zn) with eight crown ether groups appending on the periphery through flexible alkylthio-bridges have been synthesized through esterification of octakis (hydroxyethylthio)-porphyrazinatomagnesium with a carboxylic acid derivative of benzo-15-crown-5 in the presence of dicyclohexyl-carbodiimid. The new compounds have been characterized by elemental analysis and IR, 1 H NMR, UV–Vis and mass spectral data. Alkali metal interaction of the crown ethers on the magnesium porphyrazinate ( 4 ) are shown to form intramolecular sandwich type adducts by the changes occurring after gradual portionwise addition of these salts into the porphyrazine solutions.